Toxic Epidermal Necrolysis (TEN) in a Patient with Human Immunodeficiency Virus: Case Report - Acosta Carreón, Edgar Nahim; Brian Artemio Perez Canul (International Journal of Medical Science and Clinical Research Studies, 2025)
Stevens-Johnson Syndrome (SJS)/Toxic Epidermal Necrolysis (TEN) is a spectrum of mucocutaneous hypersensitivity reactions. This report details the case of an18-year-old male patient with a history of HIV who developed extensive skin lesions and mucosal involvement after using carbamazepine. The diagnosis was confirmed clinically, and it was treated with intravenous corticosteroids, crystalloid solutions, supportive care, and discontinuation of the implicated drug, resulting in favorable clinical evolution. This case highlights the importance of early recognition of SJS/TEN and immediate withdrawal of the causative agent to improve prognosis.